Antioxidant and Anti-Aging Potential of Indonesian Local Fruits: A Systematic Review - Made Ayu Mirah Wulandari; Siti Mar’atul Munawaroh; Aris Widiyanto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Skin aging is a complex biological process characterized by oxidative stress, degradation of extracellular matrix components, increased activity of matrix-degrading enzymes, and altered cellular signaling pathways. Natural products rich in bioactive compounds, particularly antioxidants, have gained increasing attention as potential anti-aging agents. Indonesian local fruits are known to contain diverse phytochemicals, including flavonoids, phenolic compounds, xanthones, and carotenoids. However, their antioxidant and anti-aging properties have not been comprehensively synthesized. This study aimed to systematically review empirical evidence regarding the antioxidant and anti-aging potential of Indonesian local fruits. This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PICO framework includes the following components: Population (P): Indonesian local fruits; Intervention (I): Fruit extract or fruit-based formulation; Outcomes (O): Antioxidant activity and anti-aging effects. PubMed, Scopus, ScienceDirect, and Google Scholar were used as sources to identify relevant articles using the keywords “Indonesian local fruit extract,” “antioxidant activity,” and “anti-aging.” Thirteen in vitro experimental studies met the inclusion criteria. The findings consistently demonstrated that various Indonesian local fruit extracts exhibited significant antioxidant activity, with several classified as strong to very strong (IC₅₀ < 50 ppm). Anti-aging effects were demonstrated through inhibition of skin-aging-related enzymes, including elastase, collagenase, hyaluronidase, and tyrosinase. Additionally, several studies reported modulation of molecular markers associated with aging, such as increased Silent Information Regulator 1 (SIRT1) expression and decreased Matrix Metalloproteinase-1 (MMP1) expression. Indonesian local fruits exhibit considerable antioxidant capacity and anti-aging potential based on in vitro evidence.